Density of red-brocket deer (Mazama americana trinitatis cetartiodactyla: cervidae) on the continental island of Trinidad, WI. Issue 1 (31st December 2023) - Rostant, Luke; Agard, J.; Devenish-Nelson, E.; Beddoe, L.; Nathai-Gyan, N.; Nelson, H.
ABSTRACT: The Trinidadian red-brocket deer ( Mazama americana trinitatis ) is the only species of deer in Trinidad and is classified as a unique subspecies of red-brocket deer. Despite the importance of the species in Trinidad, to date there have been no published studies on their densities. We report on the densities of this species at four different sites in Trinidad over a 3-year period, with the first 2 years sampled during a hunting moratorium. Diurnal surveys were conducted, with density estimates calculated using King's Estimator. Surveys were repeated in both the dry and rainy seasons. A total of 312 deer on 1131.4 km of transect were observed over the study. Density estimates varied between different sites (1–16 individuals/km 2 ), and between one and eight individuals/km 2 island-wide. Overall, the estimated density of red-brocket deer increased in two of four sites during the study period, indicating that the institution of the moratorium may have had a positive impact on populations of deer. The fact that density estimates varied considerably across the island suggests that harvest levels may need to be tailored for different sites.